Aplicación de un sistema de gestión de seguridad para disminuir los accidentes en la recuperación de puentes y pilares de la zona Las Torres, concesión de la empresa minera Marsa - Quispe Otiniano, Geiner Joel (2020)
This research paper analyzes an application of a Work Safety Management System based on Law No. 29783 and D.S. 023-2017-EM in the company called Comunidad Campesina de Llacuabamba dedicated to mining works to recover bridges and pillars in the concession of the mining company Marsa. The system will enable the enterprise to manage the risks associated with its operations to provide a safe working environment by preventing the occurrence of occupational accidents and diseases; and thus achieve compliance with the country’s current legal regulations. A situational diagnosis was made with regard to the number of accidents, operations and compliance with ministerial resolution No. 050-2013- TR, with 41.31% compliance being determined as average total when evaluating the guidelines for: commitment and involvement, security policy, organization of security management system, planning and implementation, implementation and operation, regulatory evaluation, verification, control of information and documents and management review. Then the design of the implementation planning of a Work Safety System was developed, involving an annual program of security, responsibilities, competencies and training, senior management, as well as supervisors and workers, the safety committee as well as operational control. Inspections were specified, as well as a contingency and emergency plan, corrective and preventive actions. Actions of continuous improvement for the constant revision of the security system were considered. Finally, the cost of implementing this proposed Security System was determined, including the necessary resources, amounting to $228 359.26. The implementation of the Safety Management System resulted in a decrease in the number of total accidents from 47 (2018) to 12 (2019), representing a 74.5 per cent reduction.